From waste to resource: Pomegranate peels as a sustainable biomaterials solution - Wan Norfazilah, Wan Ismail (Elsevier Ltd, 2025)
This chapter presents an analysis of how pomegranate peels can contribute as a sustainable biomaterial solution. Typically discarded as food waste, these peels possess significant potential to be repurposed into useful biomaterials applicable in various areas such as packaging, preservative, and insulation. The inherent qualities and chemical makeup make pomegranate peels a compelling alternative to synthetic and nonsustainable materials. The topic of discussion in this chapter revolves around pomegranate peel extraction and subsequent processing methods, characterization of the resultant biomaterials, and identifying their potential applications. Furthermore, these findings are compared against other existing fruit peel waste biomaterial solutions to ascertain which one stands out as more viable. Lastly, some insights into current obstacles faced by pomegranate peel and its future directions as a sustainable option are highlighted.